HO CHI MINH’S THOUGHTS ON THE PARTY’S RESPONSIBILITY IN NATION UNITY TO BUILD REVOLUTIONARY FORCES AND CURRENT ORIENTATION VALUES - Nguyen Chi Thien; Bui Van Ha; Hoang Thi Hong Hanh (Journal of Applied Science and Technology, 2019)
National unity is a precious tradition from thousands of years of the Vietnamese nation. Thanks to the tradition of solidarity, the Vietnamese people have maintained the borders of the country, build up an independent, self-reliant nation. Acquire traditional lessons of the nation, after building the Communist Party of Vietnam, Ho Chi Minh said that, the Party must perform the task of national unity, to mobilize forces to bring the revolutionary cause of the nation to complete victory. This system of his is still valid for the Vietnamese Communist Party in gathering, expand the block of national unity in the current period.